CLASSICAL EXPERIMENT IN CINE MUSIC: सिने संगीत में शास्त्रीय प्रयोग - Vahne, Lokesh (International Journal of Research -GRANTHAALAYAH, 2015)
Music is an excellent fine art whose main basis is the sound or voice, hence the art of rasa is called naad brahma. We can call this art a combination of the tone that makes the heart’s feelings of the artist melodious and reveal it to others, so music is considered to be the language of the heart and the language to express the heart feelings, says the English scholar Ruskin The upliftment of the soul and giving it artistic artistic form should be the main objective of music. Self Rabindranath Tagore also considered it to be a real and lively performance of beauty, this art has a close relationship with animals, humans and animals also sacrifice their lives on it, music is just amritaras for animals. संगीत एक उत्कृष्ट ललित कला है जिसका मुख्य आधार नाद अथवा आवाज है इसी कारण रस कला को नाद ब्रह्म पुकारा गया है। इस कला को हम स्वरांे का ऐसा सम्मिश्रण कह सकते हैं जो कलाकार की हृदयगत भावनाओं को मधुर बनाकर दूसरों के सामने प्रकट करता है इसलिए संगीत को हृदय की भाषा तथा हृदयगत भावनाओं को प्रकट करने की भाषा माना जाता हैं अंग्रेज विद्वान रस्किन कहते है, ’’अन्तरात्मा का उत्थान तथा उसे कलात्मक आन्नदमय स्वरूप प्रदान करना ही संगीत का मुख्य उद्देश्य होना चाहिए। स्व. रविन्द्रनाथ टैगोर ने भी इसे सौन्दर्य का साकार एवं सजीव प्रदर्शन माना हैं, इस कला का प्राणीमात्र से घनिष्ठ सम्बन्ध है, मनुष्य ही क्या पशु भी इस पर अपने प्राण न्यौछावर करते हैं संगीत प्राणी मात्र के लिए अमृतरस है।